Calcium/Calmodulin-Dependent Protein Kinase II Inhibitors Mitigate High-Fat Diet–Induced Obesity in Mice - Naoyuki Kawao; Ryosuke Satoh; Yuya Mizukami; Katsumi Okumoto; Genzoh Tanabe; Osamu Muraoka; Reiko Sugiura; Hiroshi Kaji (Journal of Obesity)
Calcium signaling contributes to obesity and its related disorders, such as diabetes. We herein investigated the effects of calcium/calmodulin-dependent protein kinase II (CaMKII) inhibitors on diet-induced obesity in mice. In mice fed a high-fat diet (HFD), the administration of the CaMKII inhibitor KN-93 and the glycolipid acremomannolipin A with the suppression of CaMKII phosphorylation reduced fat mass in the whole body, epididymal and subcutaneous white adipose tissue weights, and lipid accumulation in epididymal and subcutaneous white adipose tissues, but not muscle mass or bone mineral density at the tibia. Moreover, the administration of KN-93 and acremomannolipin A improved glucose intolerance in HFD-fed mice. In an in vitro study on preadipocytic 3T3-L1 cells and mouse adipose tissue-derived stromal cells, KN-93 and acremomannolipin A suppressed adipogenic differentiation, proliferation, and lipid accumulation. In conclusion, this is the first study to demonstrate that CaMKII inhibitors mitigated the development of diet-induced obesity in mice partly through the suppression of adipogenic differentiation, cell proliferation, and lipid accumulation in adipocytes. Inhibiting CaMKII could be a potential strategy for obesity treatment.